Розвиток репродуктивних структур у деяких видів роду Spiraea L. i Aruncus sylvestris Rafin. (Spireoideae, Rosaceae) - Попович, Г.Б. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2009)
Исследованы формирование структурно однополых цветков у Aruncus sylvestris Rafin. и органогенез цветка у представителей рода Spiraea L. (Rosaceae). Семяпочка красинуцелятная с одним интегументом. Количество археспориальных клеток вариабельно. Зародышевый мешок нормального Polygonum-типа. Семенная репродукция осуществляется половым путем. Эндосперм нуклеарный. Зародыш развивается по типу Asteradvar. Geum. Formation of structurally unisexual flowers has been investigated in Aruncus sylvestris Rafin. Organogenesis of the flower has been studied in the genus Spiraea L. (Rosaceae). The ovule is crassinucellate with one integument. The number of archesporium cells is variable. The embryo sac is of the normal Polygonum-type. The seed reproduction as is usually sexual, endosperm nuclear. The embryo develops by the type Asterad var. Geum.